Profile and risk factors in farmer injuries: a review based on Haddon matrix and 5 E’s risk reduction strategy - Qi, Xuejie; Yao, Xue; Cong, Xianzhu; Li, Shuang; Han, Mei; Tao, Zikun; Yang, Xi; Qi, Xiao; Shi, Fuyan; Wang, Suzhen (Frontiers in Public Health, 2024)
Farmers are considered a high-risk group for intentional and unintentional injuries. This review identified significant risk factors for agricultural injuries in farmers and explored injury prevention countermeasures based on the literature. Therefore, CiteSpace software was used to analyze the relevant literature in this field. Additionally, we identified both key risk factors and countermeasures using the Haddon matrix and the 5 E’s risk reduction strategies conceptual framework, respectively. The risk factors were identified from four categories (host, agent, physical environment, and social environment) corresponding to three phases (pre-event, event, and post-event). Interventions of 5 E’s risk reduction strategies including education, engineering, enforcement, economic, and emergency response have been proven effective in preventing injuries or reducing their severity. Our findings provide a comprehensive foundation and research direction for the study and prevention of injuries among farmers.